(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This paper analyzes similarities and differences between the Skinnerian descriptions of the behaviors traditionally called problem solving, self-remembering, self-control, decision-making, and creativity. We read the chapters in which Skinner describe contingencies that evoke the term “creativity” and terms related by this author, identifying common characteristics and differences in the proposed descriptions. Such an analysis highlights the occurrence of precurrent behaviors by which the environment is manipulated by the individual in order to increase (or decrease) the probability of a response by him/herself as the main similarity between the cases discussed. The differences are in the reinforcing consequences, characteristics of antecedent situation and elements of contingencies that can be specified prior to the emission of the response. We discuss the possibilities opened by this description for experimental investigation of creative behavior and for applications of Behavior Analysis interested in strengthening the production of creative behaviors.